STUDI DESKRIPTIF PERSIAPAN DOKUMEN AKREDITASI PUSKESMAS 2015 TENTANG PEMBAKUAN KODE DI PUSKESMAS NANGGULAN KULON PROGO - Ida Ayu Nur Faiza; Rawi Miharti (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background: In the era of the ASEAN Free Trade Area (AFTA), the quality of health services is required to compete internationally. The data of diagnostic and procedure is one of the determinants of service quality. One of the ways to improve the quality of health services is to carry out accreditation. Puskesmas Nanggulan Kulon Progo prepared the documents about standardisation of code for Puskesmas Accreditation 2015. Furthermore, in National Health Insurance program (Jaminan Kesehatan Nasionalprogram) diagnostic and procedure codes are used as the terms to claim to Badan Penyelenggara Jaminan Sosial (BPJS). Objective: This research aimed to explore the documents preparation of Puskesmas Accreditation 2015 regarding code standardisation at Puskesmas Nanggulan Kulon Progo. Method: This research was a descriptive research with a qualitative approach. The design of the research used in this study was phenomenology. Data collection technique in this study was observation towards the documents of accreditation related to codestandardisation and interview withfive respondents who involvedin the accreditation team. Results: The documents preparation forPuskesmas Accreditation 2015 regardingcodestandardisation was successfully completed. The preparation for accreditation related to code standardisation were as follow: Man: planing the finance scheme,prepare documents related to accreditation, form a team of accreditation documents arrangement Method: process of forming a team that will arrange the documents and the process of preparing the documents Materials: preparing stationery for office use Machines: preparing laptop (or computers) and printer Money : meeting all the financial Conclusion:Documents preparation towards Puskesmas accreditation require human resource, methods, materials, machines, and fund. Keywords: Accreditation, accreditation preparation, puskesmas accreditation, 5M, standardisation of the code.